CoSe2/MoSe2 Heterostructures with Enriched Water Adsorption/Dissociation Sites towards Enhanced Alkaline Hydrogen Evolution Reaction. Issue 43 (29th June 2018) - Zhao, Guoqiang; Li, Peng; Rui, Kun; Chen, Yaping; Dou, Shi Xue; Sun, Wenping
Abstract: Transition‐metal dichalcogenides (TMDs) are promising electrocatalysts toward the hydrogen evolution reaction (HER) in acid media, but they show significantly inferior activity in alkaline media due to the extremely sluggish water dissociation kinetics. Herein, CoSe2 /MoSe2 heterostructures with CoSe2 quantum dots anchored on MoSe2 nanosheets are synthesized towards enhanced alkaline HER catalytic activity. The incorporation of CoSe2 is intended to construct additional water adsorption sites on the basal planes of MoSe2 to promote water dissociation. The CoSe2 /MoSe2 heterostructures show substantially enhanced activity over MoSe2 and CoSe2 in 1 m KOH. The optimal overpotential required to reach a current density of 10 mA cm −2 is merely 218 mV, which is more than 100 mV greater than that of MoSe2, which is by far the best performance demonstrated for precious‐metal‐free catalysts. Detailed analyses based on electrochemical testing demonstrate that the water adsorption and subsequent dissociation process is accelerated by CoSe2 species with rich edge sites; meanwhile, MoSe2 species provide sufficient active sites for the adsorption and combination of adsorbed hydrogen (H . ). These results provide an effective strategy for developing earth‐abundant catalysts with high activity for the alkaline HER, and are of great significance to promote the practical application of alkaline water electrolysis. Abstract : Sites to split : Highly active transition‐metal dichalcogenide (TMD)‐based heterostructures are designed and synthesized by constructing water adsorption sites on MoSe2 nanosheets surface for application in the alkaline hydrogen evolution reaction (HER; see figure). The results provide an effective strategy for developing earth‐abundant catalysts with high activity for the alkaline HER and application in alkaline water electrolysis.